2011
DOI: 10.3141/2234-07
|View full text |Cite
|
Sign up to set email alerts
|

Transportation and Emergency Management Tool Kit for Communications with Vulnerable Populations

Abstract: Communication with vulnerable populations about transportation in emergency situations contains serious gaps. Earlier case studies notwithstanding, the lessons of Hurricane Katrina provided a major impetus to legislation, studies, and action. Much legislation advises that community-based organizations should be worked with to bridge the gaps, but little guidance is given. TCRP funded an effort to create such a tool kit for transportation and emergency managers. The study culminates in spring 2011; this paper p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 2 publications
(1 reference statement)
0
4
0
Order By: Relevance
“…Characteristics common among carless populations-including disability, isolation, age, poverty and language barriers-often impede communication between community leaders, government officials and individuals [29,31]. Secondly, (2) inventorying available transportation resources and matching these resources with evacuation demand at a regional scale is necessary to systematically execute a large-scale evacuation [23], but is typically not undertaken by local officials [43].…”
Section: Barriers To Multi-modal Evacuation: a Review And Synthesismentioning
confidence: 99%
“…Characteristics common among carless populations-including disability, isolation, age, poverty and language barriers-often impede communication between community leaders, government officials and individuals [29,31]. Secondly, (2) inventorying available transportation resources and matching these resources with evacuation demand at a regional scale is necessary to systematically execute a large-scale evacuation [23], but is typically not undertaken by local officials [43].…”
Section: Barriers To Multi-modal Evacuation: a Review And Synthesismentioning
confidence: 99%
“…People with barriers to accessing transportation in an emergency may also experience obstacles to receiving information about how to accept assistance before and during an emergency. Communication barriers are often caused by the same factors that affect the carless population; these barriers may include disability, limited English proficiency, isolation, age, and poverty (42,43).…”
Section: Identifying and Communicating With Households That Do Not Have Vehiclesmentioning
confidence: 99%
“…9p601 For risk communication involving the general public and vulnerable populations, Campbell et al 17p2 underscore the need to adhere to three common and long-standing principles: "Communicate through familiar and trusted messengers; provide clear, actionable information; and tailor messages and information pathways for target audiences." Best practices recommended by others include: maximizing the use of trusted local media channels, developing risk communication products through collaborative partnerships with local organizations, 18 understanding the needs and priorities of partners, 18,19 and ensuring the risk communication process and products are context-specific. 13,20 Risk communication research has also demonstrated that effective disaster preparedness campaigns require multiple vectors of credible and consistent information delivered by trusted messengers.…”
Section: Introductionmentioning
confidence: 99%